Efektivitas Pembelajaran Blended Learning Dalam Mata Pelajaran Bahasa Indonesia Di Era New Normal - Salsabila, Salsabila; Nurmina, Nurmina (Aliterasi (Jurnal Pendidikan, Bahasa, dan sastra), 2022)
ABSTRACT This study aims to describe the data on differences in student learning outcomes through a blended learning model using conventional learning multimedia in non-fiction text material. This study uses a quantitative approach. This type of research is quasi-experimental. The population in this study were all class XII students of MAN 2 Ireuen for the academic year 2020/2021 as many as seven classes with a total of 155 students. Sempl in this study were class XII IPA 1 as many as 24 students as the experimental class and class XII IPS as many as 24 students as the control class. Collecting data using pre-test and post-test. The data analysis technique used 1) normality test 2) homogeneity test and 3) hypothesis test. The results obtained that tcount < ttable is 1.72 > 1.68. Thus, H0 is rejected and Ha is accepted. it can be concluded that there are differences in student learning outcomes through the implementation of blended learning learning models using multimedia with student learning outcomes taught using conventional learning models in non-fiction text learning to students. Keywords: blended learning, multimedia, non-fiction text.